Characteristics study of a simple passive multiband receiver / Mohd Hazrie Samat - Samat, Mohd Hazrie (2013)
A passive multiband receiver is a one of the group of frequencies system which receives only. Basically, it is an amplified type of "crystal radio" designed to receive AM transmissions. The "passive" design uses no oscillators or other radio frequency circuitry capable of interfering with any communications system. This study discusses the characteristics of the passive multiband receiver by observe the effect of potentiometer, inductor and capacitor to the voltage range as replacement for the frequency range. This study was carried out by build a simple passive multiband receiver circuit. Then, measurement of the input voltage and output voltage is conducted. From the data obtained, calculation for voltage gain is made. This study found that the voltage range for the receiver will presented in the graph. Lastly, the multiband receiver is type of radio wave that is important to carry information from one place to another by using air as a medium.